Intermediate filaments in the heart: The dynamic duo of desmin and lamins orchestrates mechanical force transmission - West Gun; Sedighi Sogol; Agnetti Giulio; Taimen Pekka (United Kingdom, 2025)
The intermediate filament (IF) cytoskeleton supports cellular structural integrity, particularly in response to mechanical stress. The most abundant IF proteins in mature cardiomyocytes are desmin and lamins. The desmin network tethers the contractile apparatus and organelles to the nuclear envelope and the sarcolemma, while lamins, as components of the nuclear lamina, provide structural stability to the nucleus and the genome. Mutations in desmin or A-type lamins typically result in cardiomyopathies and recent studies emphasized the synergistic roles of desmin and lamins in the maintenance of nuclear integrity in cardiac myocytes. Here we explore the emerging roles of the interdependent relationship between desmin and lamins in providing resilience to nuclear structure while transducing extracellular mechanical cues into the nucleus.